A retrospective analysis of nursing documentation in the intensive care units of an academic hospital in the Western Cape - Hector, Dawn (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MCur (Interdisciplinary Health Sciences. Nursing Science))--University of Stellenbosch, 2010.